Arhitova krivulja - Razpet, Marko (Obzornik za matematiko in fiziko, 2015)
In this contribution the Archytas curve is presented. It is usually mentioned in connection with the ancient problem of doubling the cube. It is created as the intersection of a horn torus and a circular cylinder which touches the torus at two points.
Keywords: matematika; mathematics; krivulje